AgOTf-catalyzed dehydrative [3+2] annulation of aziridines with 2-naphthols - Kaicharla, Trinadh; Jacob, Anu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2017)
The reaction of 2-naphthols with aziridines in the presence of AgOTf resulting in a dehydrative, formal [3+2] annulation is reported. The reaction allows the synthesis of functionalized benzoindolines, and tolerates a broad range of functional groups. A preliminary study on themechanism of this reaction indicates an SN1-type ring-opening of aziridines. This method is demonstrated for the one-pot synthesis of benzoindoles.

Metal-free, brønsted acid-catalyzed formal [3+2] annulation of quinone monoacetals with 2-naphthols - Jacob, Anu; Roy, Tony; Kaicharla, Trinadh; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
An operationally simple and metal-free cross-coupling of quinone monoacetals (QMAs) with 2-naphthols catalyzed by triflic acid is reported. This formal [3+2] annulation allowed the synthesis of diverse naphtho[2,1-b]benzofuranderivatives in moderate to good yields. Preliminary mechanistic studies reveal the initial nucleophilic substitution of QMAs with 2-naphthols in preference to the mixed acetal formation and subsequent [3,3] sigmatropic rearrangement.

[8+3]-cycloaddition of tropones with azaoxyallyl cations - Roy, Tony; Jacob, Anu; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemistry-An Asian Journal, 2019)
Although azaoxyallyl cations are widely used as 1,3-dipoles for various cycloaddition reactions leading to nitrogen-containing heterocycles, their application in higher-order cycloaddition reaction remains scarce. Herein, we present the [8+3]-cycloaddition reaction of tropones with in situ generated azaoxyallyl cations allowing the one-step construction of cycloheptatriene-fused 1,4-oxazinones in moderate to good yields. This base-promoted new carbon-oxygen and carbon-nitrogen bond-forming reaction takes place under mild conditions in the absence of transition metal catalysts.
Keywords: 1; 4-oxazinones; azaoxyallyl cations; heterocycles; tropones; [8+3] cycloaddition